2017
DOI: 10.1038/s41598-017-07575-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-23-TrxR1 as a novel molecular axis in skeletal muscle differentiation

Abstract: Thioredoxin reductase 1 (TrxR1) is a selenocysteine-containing protein involved in cellular redox homeostasis which is downregulated in skeletal muscle differentiation. Here we show that TrxR1 decrease occurring during myogenesis is functionally involved in the coordination of this cellular process. Indeed, TrxR1 depletion reduces myoblasts growth by inducing an early myogenesis -related gene expression pattern which includes myogenin and Myf5 up-regulation and Cyclin D1 decrease. On the contrary, the overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 49 publications
1
21
2
Order By: Relevance
“…Either loss- and gain-of-function experiments have shown that miR-208b and miR-499 play important roles in muscle fiber identity by activating slow and repressing fast myofiber gene program [ 82 , 83 ]. Several other studies have shown that after 3 hours of one acute exercise miR-1, miR-133a, miR-133-b and miR-181a were all increased [ 10 , 84 , 85 ] whereas, miR-9, miR-23a, miR-23b and miR-31 decreased (Table 2 ). In another study, Nielsen and colleagues (2010) demonstrated that miR-1 and miR-133a expression levels in the vastus lateralis of healthy individuals were significantly upregulated after only one cycle ergometer activity at 65% of maximal power (Pmax).…”
Section: Mirna Functions In Skeletal Muscle Regenerationmentioning
confidence: 95%
“…Either loss- and gain-of-function experiments have shown that miR-208b and miR-499 play important roles in muscle fiber identity by activating slow and repressing fast myofiber gene program [ 82 , 83 ]. Several other studies have shown that after 3 hours of one acute exercise miR-1, miR-133a, miR-133-b and miR-181a were all increased [ 10 , 84 , 85 ] whereas, miR-9, miR-23a, miR-23b and miR-31 decreased (Table 2 ). In another study, Nielsen and colleagues (2010) demonstrated that miR-1 and miR-133a expression levels in the vastus lateralis of healthy individuals were significantly upregulated after only one cycle ergometer activity at 65% of maximal power (Pmax).…”
Section: Mirna Functions In Skeletal Muscle Regenerationmentioning
confidence: 95%
“…In addition, previous studies have also demonstrated that the expression of miR-23 is dysregulated in angiogenesis, coronary artery disease, immune responses and cancer (15)(16)(17)(18)(19); the dysregulation of miR-23 is associated with numerous of cancer (20)(21)(22). The miR-23 protein family has two members: mir-23a and mir-23b (23). Cai et al (20) demonstrated that the levels of miR-23a were decreased in prostate cancer and that low levels of miR-23a were associated with poor prognosis.…”
Section: Mir-23b-3p Promotes the Apoptosis And Inhibits The Proliferamentioning
confidence: 99%
“…However after chronic exercise, miR-1 and miR-133b were downregulated in a majority of studies [50,[55][56][57]. Only two studies reported increased expression of miR-133b and miR-181 which is thought to be associated with increased glucose homeostasis [40,60], and another study found a decrease in miR-23 [51] involved in myogenic processes [61]. A case-control study comparing powerlifters to healthy controls [58] reported a unique miR expression profiles that were able to distinguish powerlifters from healthy controls based on a five miR signature (miR-126, −23b, −16, −23a, −15a).…”
Section: Mirnas and Exercisecandidate Gene Approachmentioning
confidence: 99%